Formação de professores: um estudo sobre a prática reflexiva acerca da avaliação no contexto PIBID/Biologia - Luiz, Cintya Fonseca (2017)
There are challenges that must be investigated to contribute to the initial education of science teachers. One of these is evaluation. Thus, we point to the commitment and responsibility of transforming teacher education through reflective practice.In this way, educating a reflective teacher contributes to possible changes in educational practical, especially the evaluative one. Therefore, it is relevant, even in the initial formation of teachers, the academic to experience practical situations, articulating the scientific knowledge of the subject that he will teach.In order to promote this articulation between the university and the schools and to contribute to the improvement of teachers education, the Institutional Scholarship Program for Teaching Initiation, known as Pibid was developed by the Coordination for the Improvement of Higher Education Personnel (Capes) -which is responsible for coordinating efforts to improve the quality of Brazil’s faculty and staff in higher education through grant programs.Considering the context of initial teacher education presented, and with the assumption that the reflective practice of the teacher of science contributes to changes in his / her evaluation practice, and also that evaluation can help to develop a reflexive practice, our research problem was: How the study on a reflexive and evaluative practice in the initial formation of teachers is related to teaching intheuniversity graduate's speech?The research was guided by the objective of identifying the understandings about the evaluation and the reflexive practice present in the discourse of graduates, as well as investigate implications of the evaluative and reflexive practice in the initial formation of teachers. To do so, the data were constituted by applying an initial and final questionnaire and the audio and video recordings of the meetings developed in the focal group formed by 12 Biological Sciences graduates participating in the Pibid / Biology Subproject of the Western Paraná State University (Unioeste).The data were analyzed based on the Textual Discursive Analysis and allowed newinsights about the initial teacher training in relation to the reflexive teacher study and evaluation of the learning, revealing the implications of the teaching practice of the university professor in the training of the graduates In the disciplinary context were submitted To contradictory assessments compared to those that are challenged to elaborate. This fact caused anguish among the graduateswhen they learned of the necessity of the teaching practice about the evaluation, but impotent for not knowinghow to do it. In this sense, we understand that reflexive practice allows the teacher's ability to investigate the practice itself, as well as the social factors that permeate it, in order to generate changes in beliefs and theories about the act of evaluating what is inculcated in the graduates. We know this process of changes in understanding is not easily transformed. However, we understand reflexive practice as an alternative for the graduatesand teachers to change the evaluative practices that are merely reproduced.